Investigating the Nexus between Financial Development and Economic Growth in SEE 10 Economies (European Journal of Marketing and Economics, 2018)
In a continuous challenge for increasing economic growth pace, Southeastern Europe economies need to explore all contributing channels to this process. Previous researches do not find a significant relation between financial development and economic growth in SEE countries but up-to-date analyses are missing in this front. This paper aims to investigate the finance-growth links in a representative group of ten SEE economies through empirically analyzing with panel data techniques the latest data available, and try to understand if implementation of financial regulatory frameworks and economic reforms during the last decade has contributed in making financial sector development significant for growth. In this context, obtained results show that credit to private sector, is the only financial development indicator that has become became significantly important in short-run in positively affecting economic growth. While Liquid liabilities and Assets ratio have no significance, seems that financial sector reforms need to continue in order to enhance the causal relation between finance and growth.
Keywords: financial institutions, financial development, economic growth Jel classification: G2, O16